Objectively Measured Daily Physical Activity and Postural Changes as Related to Positive and Negative Affect Using Ambulatory Monitoring Assessments. Issue 7 (September 2017) - Aggio, Daniel; Wallace, Karen; Boreham, Nicola; Shankar, Aparna; Steptoe, Andrew; Hamer, Mark
ABSTRACT: Objective: The aim of the study was to determine whether objectively measured daily physical activity and posture of sitting, standing, and sit-to-stand transitions are associated with daily assessments of affect. Methods: Participants ( N = 51, 49% female) wore ActivPal accelerometers for 24 h/d for seven consecutive days. Time spent sitting, standing, and being physically active and sit-to-stand transitions were derived for each day. Participants also completed a mood inventory each evening. Multilevel models examined within- and between-person associations of daily physical activity with positive and negative affect, adjusting for age, sex, body mass index, education, and sleep duration. Results: Within-person associations showed that a 1-hour increase in daily physical activity was associated with a decrease in negative affect over the same day ( B = −0.11, 95% confidence interval [CI], −0.21 to −0.01). Between-person associations indicated a borderline significant association between higher average daily physical activity levels and higher positive affect ( B = 1.85, 95% CI = −0.25 to 3.94). There were no between- or within-person associations between sitting, standing, and sit-to-stand transitions with affect. Conclusions: Promoting physical activity may be a potential intervention strategy to acutely suppress negative affective states. Abstract : Supplemental digital content is available in the text.